Power in the blood : a family narrative - Tate, Linda (Ohio University Press series in race, ethnicity, and gender in Appalachia., 2009)
Power in the Blood: A Family Narrative traces Linda Tate's journey to rediscover the Cherokee-Appalachian branch of her family and provides an unflinching examination of the poverty, discrimination, and family violence that marked their lives. In her search for the truth of her own past, Tate scoured archives, libraries, and courthouses throughout Kentucky, Tennessee, Alabama, Illinois, and Missouri, visited numerous cemeteries, and combed through census records, marriage records, court cases, local histories, old maps, and photographs. As she began to locate distant relatives - fifth, sixth,